Assessment the effect of exposure to microplastics in Nile Tilapia (Oreochromis niloticus) early juvenile: I. blood biomarkers. (August 2019) - Hamed, Mohamed; Soliman, Hamdy A.M.; Osman, Alaa G.M.; Sayed, Alaa El-Din H.
Abstract: There is a scarcity of knowledge about the impacts of microplastics (MPs) on the early juvenile stage of freshwater fish. The current study aims to inspect the exposure and post-exposure recovery of microplastics (MPs) on accumulation and blood biomarkers of Nile Tilapia ( Oreochromis niloticus ) early juvenile. Four groups of fishes were used; the first group was the control group, the second group was exposed to (1 mg/L of MPs), the third group was exposed to (10 mg/L of MPs), and the fourth group was exposed to (100 mg/L of MPs) for 15 days and 15 days of recovery. The results showed that significantly higher numbers of microplastics were observed in microplastics-exposed groups compared to control group. Biochemical parameters (creatinine, uric acid, AST, ALT, ALP, glucose, cholesterol, total protein, albumin, globulin, and A/G ratio) showed significant increment after exposure to microplastics for 15 days compared to control group in dose dependent manner. The hematological indices (RBC's count, Hb, Ht, MCHC, Platelets, WBC's count, and monocytes) showed a significant decline after exposure to microplastics for 15 days compared to control group, while MCV and MCH showed a significant increase after exposure to microplastics for 15 days. After the recovery period, microplastics accumulations, hemato-biochemical alterations were still detected in microplastics exposed groups compared to the control group except for WBC's count and MCV which return to normal levels. MPs caused anemia and perturbations in hemato-biochemical parameters which may cause mortality of tilapia early juvenile and should be considered in a program for monitoring hazard materials in the ecosystem. Graphical abstract: Image 10513460 Highlights: Microplastics (MPs) are accumulated in whole body of tilapia early juvenile. Microplastics (MPs) induced anemia and perturbations in biochemical parameters. The effect of Microplastics (MPs) is both concentration and time dependent.